Identification of New CTX Analogues in Fish from the Madeira and Selvagens Archipelagos by Neuro-2a CBA and LC-HRMS - Àngels Tudó; Maria Rambla-Alegre; Cintia Flores; Núria Sagristà; Paloma Aguayo; Laia Reverté; Mònica Campàs; Neide Gouveia; Carolina Santos; Karl B. Andree; Antonio Marques; Josep Caixach; et al. (Marine Drugs, 2022)
Ciguatera Poisoning (CP) is caused by consumption of fish or invertebrates contaminated with ciguatoxins (CTXs). Presently CP is a public concern in some temperate regions, such as Macaronesia (North-Eastern Atlantic Ocean). Toxicity analysis was performed to characterize the fish species that can accumulate CTXs and improve understanding of the ciguatera risk in this area. For that, seventeen fish specimens comprising nine species were captured from coastal waters inMadeira and Selvagens Archipelagos. Toxicity was analysed by screening CTX-like toxicity with the neuroblastoma cell-based assay (neuro-2a CBA). Afterwards, the four most toxic samples were analysed with liquid chromatography-high resolution mass spectrometry (LC-HRMS). Thirteen fish specimens presented CTX-like toxicity in their liver, but only four of these in their muscle. The liver of one specimen of Muraena augusti presented the highest CTX-like toxicity (0.270 ± 0.121 µg of CTX1B equiv·kg−1). Moreover, CTX analogues were detected with LC-HRMS, for M. augusti and Gymnothorax unicolor. The presence of three CTX analogues was identified: C-CTX1, which had been previously described in the area; dihydro-CTX2, which is reported in the area for the first time; a putative new CTX m/z 1127.6023 ([M+NH4]+) named as putative C-CTX-1109, and gambieric acid A.